2020
DOI: 10.1507/endocrj.ej19-0478
|View full text |Cite
|
Sign up to set email alerts
|

Overestimation of glomerular filtration rate calculated from serum creatinine as compared with cystatin C in patients with subclinical hypercortisolism: Hyogo Adrenal Metabolic Registry

Abstract: The skeletal muscle mass are decreased in the patients with hypercortisolism. Glomerular filtration rate (eGFR) is not accurately evaluated by calculation from serum creatinine (eGFRcre) in these patients. However, it is not known whether it applies to patients with subclinical hypercortisolism. We investigated the dissociation between eGFRcre and eGFR calculated from cystatin C (eGFRcys) in patients with subclinical hypercortisolism and its association with the skeletal muscle mass. This cross-sectional study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…The vast majority of transplant patients are prescribed exogenous glucocorticoids (GCs), such as prednisolone or dexamethasone, as part of their immunosuppressive regimen 14 . Paired analyses accounting for patient-specific factors and renal function have demonstrated that exogenous GCs increase CyC production 15 , an effect that has also been observed in patients with excess endogenous GC production (Cushing's syndrome) 16 . Moreover, CyC production is increased in a range of disease states that induce GC elevations, including viral infection 17 , inflammatory disease 10 and cancer 18 .…”
Section: Introductionmentioning
confidence: 89%
“…The vast majority of transplant patients are prescribed exogenous glucocorticoids (GCs), such as prednisolone or dexamethasone, as part of their immunosuppressive regimen 14 . Paired analyses accounting for patient-specific factors and renal function have demonstrated that exogenous GCs increase CyC production 15 , an effect that has also been observed in patients with excess endogenous GC production (Cushing's syndrome) 16 . Moreover, CyC production is increased in a range of disease states that induce GC elevations, including viral infection 17 , inflammatory disease 10 and cancer 18 .…”
Section: Introductionmentioning
confidence: 89%
“…The differences may be caused by different methods used for muscle tissue assessment (Delivanis et al assessed abdominal computed tomography, whereas the Korean team used bioelectrical bioimpedance analysis) or selection bias (Delivanis et al recruited patients from an adrenalectomy database – which means that patients with non-functioning adrenal tumours might be not a representative group, because they had bigger tumours or indeterminate imagining characteristics). Interestingly Naka et al in 2020 compared GFR calculated from creatinine to cystatin C. GFR calculated from creatinine was overestimated in patients with mASC, which can be partially explained by muscle mass changes – creatinine GFR to cystatine C GFR ratio are inversely associated with skeletal muscle index 94 .…”
Section: Introductionmentioning
confidence: 99%
“…Finally, one has to bear in mind that cystatin C levels are not only altered in several clinical conditions such as hyperthyroidism and hypercortisolism, 4 but might also be endogenously increased in specific diseases (eg in lung fibrosis) 5 . Considering these influences, treatment of the underlying condition with corticosteroids would decrease elevated serum cystatin C, as has been reported among patients with asthma 6 …”
mentioning
confidence: 98%